Pathogenicity of field and laboratorygrown inoculum of Neonectria galligena on potted apple trees - Scheper, R.W.A.; Fisher, B.M.; Wood, P.N. (New Zealand Plant Protection, 2010)
European canker caused by Neonectria galligena is an important disease of apple trees worldwide In this study methods were developed for conidium production in culture and for testing the pathogenicity of N galligena Conidia produced in culture were one or twocelled while conidia collected from cankers were multicelled Isolate ICMP9472 produced enough conidia in culture to produce inoculum (210 5 conidia/ml) to test the pathogenicity in comparison with that of conidia harvested from apple cankers from Motueka (field inoculum) and a twodayold suspension of conidia from Motueka apple cankers on potted Royal Gala trees in a glasshouse under continual misting The germination rates of the three inocula were similar (5079) Two months after inoculation all inoculated wounds were infected regardless of inoculum source However cankers caused by field inoculum (fresh and two dayold) were significantly larger (average 108 mm and 106 mm respectively) than those caused by isolate ICMP9472 (51 mm) Six months after inoculation cankers caused by fresh field inoculum were significantly larger than those caused by 2dayold inoculum which were significantly larger than those caused by isolate ICMP9472 In addition cankers caused by fresh field inoculum were significantly more active than those caused by older field inoculum or isolate ICMP9472